Health behaviors regarding diet dependent on religious belief on the example of the followers of the Seventh-day Adventist Church, Islam, and Judaism - Jaksz-Recmanik, Ewelina; Puzoń, Irena (Nursing Problems / Problemy Pielęgniarstwa, 2014)
According Cockerhama health behaviors are “conscious patterns of behavior related to health, which is a result of choices made by people on the basis of available and determine of their situation in life alternatives”. One of the elements of health behavior is diet. It is an important part of everyone’s life style and determined not only health, culinary tastes, but also to a large part religion. The followers of the different religions pay special attention to what they eat. Therefore, it is important that medical staff know the rules on both diets as well as the remaining elements of lifestyle in order to avoid misunderstanding different behaviors and make changes to the care of patients of different faiths through its optimization.